1996
DOI: 10.1002/(sici)1097-0010(199604)70:4<453::aid-jsfa521>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Film-Forming Gums in thePreservation of Salted and Dried IndianMackerel (Rastrelliger kanagurtaCuvier)

Abstract: Curing preservation of fish is the most popular method in the developing countries and India is no exception. Different film‐forming gums, namely sodium alginate, tamarind kernel powder, guar gum and agar agar were tried to find their effect in preservation of salted and dried mackerel and in extending the shelf‐life of these products. Various biochemical, microbiological and organoleptic parameters were recorded during the storage period. The treatment of salted dried fish with gum solutions and subsequent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
3
4
0
Order By: Relevance
“…The variation in moisture content may be dependent on external temperature and RH during storage. Diffusion of gases and vapor through packaging material may be responsible for increase in moisture content (Palling 1980;Shetty et al 1996). Rao (1980) reported that if product contains less than 9% of moisture, it is safe for storage.…”
Section: Resultssupporting
confidence: 93%
“…The variation in moisture content may be dependent on external temperature and RH during storage. Diffusion of gases and vapor through packaging material may be responsible for increase in moisture content (Palling 1980;Shetty et al 1996). Rao (1980) reported that if product contains less than 9% of moisture, it is safe for storage.…”
Section: Resultssupporting
confidence: 93%
“…The decrease of fat content of dried shrimp samples might be attributed to the lipid oxidation occurs during drying process and the storage period. These results were found to be within obtained by Shetti (1996) and Galhom (2002).In this concern, Abd El-Qader, (2014) reported that the decrease in fat content of dried chicken during storage period might be due to the hydrolysis of fat by some microorganisms or endogenous meat enzymes in addition to auto oxidation of fat by O 2 .…”
Section: Gross Chemical Composition Of Dried Shrimp Samplessupporting
confidence: 78%
“…Guar gum film shows Fig. 6 Oxygen permeability of the films Cellulose pronounced desorption hysteresis in equilibrium moisture content and can act as barrier to air and moisture (Keating et al 2013;Shetty et al 1996). The composite films showed lower WVP than TOCNs film, indicating that the introduction of HPG effectively reduced the WVP of the composite films.…”
Section: Contact Anglementioning
confidence: 99%